2011
DOI: 10.1111/j.1365-2796.2011.02384.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition in chronic heart failure: low circulating levels of eicosatetraenoic acid and high levels of vaccenic acid are associated with disease severity and mortality

Abstract: Abstract. Øie E, Ueland T, Dahl CP, Bohov P, Berge C, Yndestad A, Gullestad L, Aukrust P, Berge RK (Research Institute for Internal Medicine, Department of Cardiology, Oslo University Hospital, Rikshospitalet, Oslo, Center for Heart Failure Research, University of Oslo, Oslo, Section of Endocrinology, Oslo University Hospital, Rikshospitalet, Oslo, Faculty of Medicine, University of Oslo, Oslo, Section of Medical Biochemistry, Institute of Medicine, University of Bergen, Bergen, Department of Heart Disease, Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…In our study, we also found positive association between FFAs and FPG ( r  = 0.239, P  < 0.05), HbA1c ( r  = 0.215, P  < 0.05), which was in consistent with previous studies [2224]. Moreover, high level of FFAs was also found to play a role in arrhythmia [25, 26] and myocardial dysfunction [2729]. Thereby, studies on the role of FFAs in predicting for atherosclerotic cardiovascular disease are benefit for improving strategies for prevention and therapy in CAD.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we also found positive association between FFAs and FPG ( r  = 0.239, P  < 0.05), HbA1c ( r  = 0.215, P  < 0.05), which was in consistent with previous studies [2224]. Moreover, high level of FFAs was also found to play a role in arrhythmia [25, 26] and myocardial dysfunction [2729]. Thereby, studies on the role of FFAs in predicting for atherosclerotic cardiovascular disease are benefit for improving strategies for prevention and therapy in CAD.…”
Section: Discussionsupporting
confidence: 91%
“…A cross-sectional study showed that HF patients have higher plasma FFA than controls 27 . In animal models, FFA were associated with cardiac dysfunction and such effect was eliminated upon treatment with fibrates 28 .…”
mentioning
confidence: 99%
“…(18,19) This was in part supported by a study showing the association of the elevated plasma levels of SFA and reduced plasma levels of DHA with the risks of HF. (20) Moreover, Oie et al (21) and Zhao et al (22) compared the changes in FA composition between the normal control and HF subjects and found out the roles of monounsaturated fatty acids (MUFAs) and some PUFA in HF subjects. They demonstrated that high levels of MUFA and linoleic acid and low levels of arachidonic acid were associated with those subjects.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that high levels of MUFA and linoleic acid and low levels of arachidonic acid were associated with those subjects. (21,22) In addition, it was reported that EPA and DHA are negatively correlated with heart rate, indicating that low proportion of either EPA or DHA increases a chance to elevate heart rate. (23) …”
Section: Discussionmentioning
confidence: 99%